Interrelationships between affective disorders in the form of depression and obesity and overweight - A systematic review - Marczak, Aleksandra; Krawczuk vel Walczuk, Julia; Maciąg , Maria; Sobczyk, Maciej; Garbacz, Karolina; Pasztelan, Małgorzata; Pulikowski, Jarosław; Muca, Aleksandra; Słaboń, Małgorzata; Baran, Joanna (Quality in Sport, 2024)
Both depression and obesity are significant health, social and economic problems. Depressive disorders were the second most common psychiatric disorder in 2017 after anxiety disorders. According to data published by the World Health Organization (WHO), depression affects about 280 million people worldwide, which is about 3.8 percent of the population. The etiology of depressive disorders is very complex and still not fully understood. The theories described so far complement each other. The factors underlying the development of depressive disorders can be divided into biological, psychological and other factors. Eating disorders in the form of overweight and obesity result from a loss of balance between anabolic and catabolic processes. This is most often led by insufficient physical activity and excess caloric intake. Hormonal disorders, genetic factors and environmental factors may also play an important role in the pathogenesis of obesity. The steadily increasing number of people suffering from depression and obesity prompts the search for links between these two seemingly unrelated disease entities. According to current knowledge, these diseases are bi-directionally linked by genetic, psychological, metabolic and social factors. Depression is associated with an increase in the risk of obesity by about 37% relative to those without depression. Obesity is associated with an increase in the risk of depressive disorders by about 18%. Understanding the links that exist between depressive disorders and obesity enables the search for new therapeutic options. The most important conclusion from the scientific research conducted so far is the advantage of simultaneous treatment of obesity and depression over treating these disease entities individually.